A Comprehensive Bibliometric Review of Material Misstatement Studies in Accounting Literature - Judijanto, Loso; Wahyudin, Wahyudin (The Es Accounting And Finance, 2026)
This study aims to explore the intellectual structure, research trends, and thematic evolution of material misstatement studies within accounting literature through a comprehensive bibliometric analysis. Using data collected from reputable databases over the period 2010–2025, this study applies bibliometric techniques, including co-occurrence analysis, network visualization, overlay visualization, and density mapping using VOSviewer. The findings reveal that early research predominantly focused on fraud detection and accounting misstatements, highlighting the role of auditing in identifying financial irregularities. Over time, the literature has shifted toward more systematic and process-oriented themes, particularly risk assessment, analytical procedures, and auditing practices. Recent trends indicate a growing emphasis on audit quality as a key outcome variable, reflecting the increasing importance of audit effectiveness, governance, and financial reporting reliability. The results also show that while core themes such as fraud and risk assessment remain highly dominant, emerging areas like audit quality are developing as distinct yet significant research streams. This study contributes to the literature by providing a comprehensive mapping of material misstatement research, offering insights into its development, current focus, and future directions. The findings suggest the need for further integration of traditional auditing approaches with emerging technologies and interdisciplinary perspectives to enhance the detection and prevention of material misstatements.